Harnessing mobile health technology to support long-term chronic illness management: exploring family caregiver support needs in the outpatient setting. Issue 4 (5th December 2020) - Shin, Ji Youn; Chaar, Dima; Kedroske, Jacob; Vue, Rebecca; Chappell, Grant; Mazzoli, Amanda; Hassett, Afton L; Hanauer, David A; Park, Sun Young; Debra, Barton; Choi, Sung Won
Abstract: Objective: Family caregiving is an important public health issue, particularly with the aging population. In recent years, mobile health (mHealth) technology has emerged as a potential low-cost, scalable platform to address caregiver support needs, and thereby alleviate the burden on caregivers. This study sought to examine the support needs of family caregivers in their lived experiences of outpatient care to inform the development of a future mHealth intervention. Materails and Methods: We conducted 20 semi-structured interviews in 2 outpatient hematopoietic cell transplant (HCT) clinics at a large academic medical center in the Midwestern United States. A thematic analysis was performed to define emerging themes. Results: Qualitative data analysis identified 5 primary themes that HCT caregivers faced: (I) lifestyle restrictions due to the patient's immunocompromised state; (II) Unmet needs due to limitations in the current resources, including unfamiliar medical tasks without necessary trainings; and (III) caregivers' adaptive strategies, including reformation of social relationships with family and friends. Based on these findings, we suggest 3 design considerations to guide the development of a future mHealth intervention. Conclusions: The findings herein captured the family caregiver's lived experiences during outpatient care. There was broad agreement that caregiving was challenging and stressful. Thus, effective and scalable interventions to support caregivers are needed. This study provided data to guide the content and design of a future mHealth intervention in the outpatient setting.